2020
DOI: 10.1038/s41398-020-00933-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of multiple peripheral inflammatory cytokine levels after repeated ketamine infusions in major depressive disorder

Abstract: Increasing evidence has demonstrated that inflammatory cytokines play an important role in major depressive disorder (MDD) and are associated with treatment outcomes. Few studies have explored the trajectories of multiple inflammatory cytokines after repeated ketamine infusions in MDD. In this study, we conducted a secondary analysis to investigate the impact of ketamine on the modulation of the inflammatory pathway in depression and whether this pathway contributes to the antidepressant properties of ketamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 61 publications
3
58
0
Order By: Relevance
“…Then, we further analyzed whether alterations in in ammatory cytokines were related to individual differences in ketamine's effects on comorbid depression and pain. We observed that most of the 19 in ammatory cytokine levels decreased from the mean change values after six infusions of ketamine treatment, consistent with our previous ndings in an overlapping sample [27]. By comparing changes in in ammatory cytokine levels after ketamine treatment, a greater decrease in IL-6 levels at 24 h after six infusions and greater decreases in IL-10, MIP-3α, IL-1β, IL-5 and IL-6 levels at two weeks after six infusions were observed in patients with pain than in patients without pain.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Then, we further analyzed whether alterations in in ammatory cytokines were related to individual differences in ketamine's effects on comorbid depression and pain. We observed that most of the 19 in ammatory cytokine levels decreased from the mean change values after six infusions of ketamine treatment, consistent with our previous ndings in an overlapping sample [27]. By comparing changes in in ammatory cytokine levels after ketamine treatment, a greater decrease in IL-6 levels at 24 h after six infusions and greater decreases in IL-10, MIP-3α, IL-1β, IL-5 and IL-6 levels at two weeks after six infusions were observed in patients with pain than in patients without pain.…”
Section: Discussionsupporting
confidence: 92%
“…Based on evidence from previous studies, ketamine may be ideal for the treatment of comorbid pain and depression, however, few clinical studies have evaluated individual differences in antidepressant outcomes to repeated ketamine infusions in patients with MDD and comorbid pain. Moreover, although plasma levels of in ammatory cytokines decreased after six infusions of ketamine administration based on our previous results [27], the roles of cytokines in ketamine's effect on concurrent pain and depressive symptoms have not been explored. In the present study, we aimed to rst determine differences in ketamine's antidepressant effects in depressed patients with and without the presence of painful symptoms and then to examine whether cytokines might contribute to ketamine's effect in depressive patients with the presence of painful symptoms.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Of these, one study stratified patients according to the responder status and found changes only in ketamine responders (Yang et al, 2015b). IL-1β decrease was observed in two out of three studies (p < 0.05; Yang et al, 2015b;Zhan et al, 2020); TNF-α in two out of five studies (p < 0.01; Chen et al, 2018;Zhan et al, 2020); IL-6 in three out of six studies (p < 0.01; Kiraly et al, 2017;Yang et al, 2015b;Zhan et al, 2020); and IFN-γ in one study out of three (p < 0.01; Zhan et al, 2020). Soluble tumor necrosis factor receptor 1 (sTNFR1) was measured in one study and was found reduced (p < 0.01; Park et al, 2017), likewise for IL-23 (Zhan et al, 2020), IL-1α, granulocyte colony-stimulating factor (G-CSF), platelet-derived growth factor (PDGF)-AA (p < 0.05), and interferon gamma-induced protein (IP)-10 ( Kiraly et al, 2017).…”
Section: Results Of Individual Studies and Evidence Synthesismentioning
confidence: 99%
“…Most studies employed treatment-resistant criteria requiring patients to have had at least two previous failed antidepressant trials, except from one study only requiring a single failed trial (Moaddel et al, 2018). Two studies allowed inclusion of nontreatment-resistant patients if these were suicidal (Zhan et al, 2020;Zhou et al, 2018). In four out of six studies, MDD patients were medication free, and in two out of three studies, BD patients were allowed mood stabilizers only.…”
Section: Description Of Selected Studiesmentioning
confidence: 99%